(untitled) (Prithvi Academic Journal, 2018)
Ageing is a normal biological process. The ageing transition reduces physiological, social and other capacities and makes elderly susceptible to social and health threats. The rich tradition of dignified ageing is drastically eroding in Nepal; hence, older people today are living in seclusion, depression, diseased and neglected by their children. The key objective of this article is to assess how the senior citizens experienced their transition of ageing. The study is pedestaled on primary data following the qualitative techniques. Healthy ageing is a multifaceted notion and one of the most intense social transformations in human history allied to physical, psychological and social experiences linked to the aged-people, immediate surroundings, friends and the society. But, amid disrupted lives, familial neglect and abandonment, the broader socio-cultural narratives on ageing transition of the elderly contain a decline as empty nesters and a very little age defying ideology. Successful aging equals active aging, hence, to keep positive self-esteem, senior citizens should be physically and mentally vibrant as well as take new responsibilities and roles, nurture new interests and develop new interactions to substitute their previous roles that have diminished with people age. Respect and mutual understanding between the older and young generation under the kinship care system is a part of oriental tradition, which needs to be sustained by state policies. This article suggests some vital measures to be addressed for a proactive dignified ageing.